OPTIMALISASI PESONA HERBAL SEBAGAI UPAYA KEMANDIRIAN DAN KETAHANAN PANGAN RUMAH TANGGA - Mustofa2), IGP Suryadarma1), Asri Widowati1) (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The activity "Optimizing of The Beauty of Herbs" is aimed: (1) to improve an understanding of the understanding of farmer group members and efficacy of herbs scientifically; (2) to improve the creativity of members of farmer groups on how the processing of various herbal products, (3)to improve awareness of farmer group members to be independent and maintain the food security. Objects of study are 45 member of farmer group " Sumber Karya Boga " in Padukuhan Pondok, Condong Catur. The methods are used in solving the problem include: lecture, workshop and practice. Stages include: the preparation stage, the introduction stage, the creative production stage, development stage and evaluation stage. Data obtained using a questionnaire about herbs and their understanding of the sources of information, selfsufficiency, food security, entrepreneurial spirit and understanding of the business plan . Results indicate that most participants have an understanding of herbs and their properties well. Participants also gain the skills to process herbs into various food products . The independence of most participants has reached "Good" category. For food security and entrepreneurial spirit obtained information that most participants have food security in the category "Good". But only few of them know about farming business plan. This suggests that they have not yet fully understand about the formulation of business plan. Keywords: the beauty of herb, food security, and enterpreneurship